Risk analysis on crucial sector priority using Analytical Hierarchy Process (AHP) and House of Risk (HoR) - Wahyukaton; FV, Mohamad Refaldi (Journal of Modern Manufacturing Systems and Technology, 2021)
There are many sectors in an company can trigger the risks, which are internal factor and external factor. By means of Risk Management, those risks can be managed. A decision making using Analytical Hierarchy Process (AHP) method was to find the elected risks as the risks mitigation then will be managed using House of Risk (HOR) method. The Risk Cost, there is a rise of Cost of Good Sold (CoGS) that can decrease the profit, was the largest risk weight, 0.132 point. And it was known that the high risk for the obstruction of target completion was caused by the shifting of most of the production schedule, so that those risks were needed to be managed and mitigated.